Gender Sensitivity in Textbooks in Secondary Education in Bhutan - Tshewang Dorji (International Journal of Asian Education, 2021)
This study was carried out to understand gender stereotype in the curriculum framework and textbooks which form the main curricular materials in schools in Bhutan. The curriculum framework for Accountancy, Economics, Mathematics, Science, Geography, History and English were reviewed by the researchers. Except for science curriculum framework which states that science curriculum should be gender-sensitive in terms of materials used, language used and ensuring the equal participation of boys and girls in activities, other frameworks were all silent on gender. Textbook reviews were carried out by teachers (22 female and 54 male) teaching classes IX to XII in the form of clustered workshops using the Blumberg model of textbook analysis which was employed to analyse gender biases in Vietnamese primary school textbooks. The findings revealed a presence of imbalance of gender among the authors, reviewers, editors and designer as well as the presence of gender biases, gender stereotyping in the content, illustrations and student activity. It calls for curriculum developers and textbooks authors to integrate gender in the curriculum framework which will then guide the development of gender-sensitive textbooks.